Exploring existence of traversable wormhole solutions in the presence of some corrected Casimir energy models - Jawad, Abdul; Rehman, Ubaid Ur; Rani, Shamaila; Övgün, Ali (World Scientific Publ Co Pte Ltd, 2022)
In this paper, we explore the wormhole solutions (which are initially proposed by R. Garattini [Eur. Phys. J. C 79 (2019) 951] who take generalized uncertainty principle (GUP) with Casimir energy) in the framework of two well-known dark energy (DE) models, generalized Chaplygin gas (GCG) and polytropic gas. We consider the GUY corrected pressure (force per unit surface area) in the equation of state (EoS) of these DE models to construct the GCG corrected energy density and polytropic gas corrected energy density. Three models of redshift function are taken into account to construct shape function as well as wormhole geometry for both cases of corrected energy densities. We find the behavior of EoS parameters, redshift function for isotropic and anisotropic fluid, equilibrium conditions, null energy condition and exotic volume at the throat of the wormhole with radius r(0).
Keywords: General relativity; wormholes; generalized uncertainty principle; Chaplygin gas